Implementasi Program SIBAKUL Jogja dalam Meningkatkan Pemasaran UMKM di Daerah Istimewa Yogyakarta - Saputra, Febi Andika; Mahendra, Gerry Katon (LP3M Universitas Dharma Wacana, 2023)
The implementation of innovation and creation in the context of marketing the products and services provided by MSME actors is very necessary, especially during the current pandemic and digitalization. This research focuses on the efforts made by the government so that MSMEs can survive, and their products can be reached by consumers in this pandemic era. This aims to increase their turnover so that they can survive and rise even when they are in a slump. The real problem for MSMEs in this pandemic era is rebuilding a sluggish economy due to a number of policies that require people to stay at home to suppress the spread of Covid-19. The research method employed a qualitative research method. This study applied data collection techniques in the form of documentation, observation, and interviews. Interviews were conducted with various MSME actors. Data analysis was carried out using inductive thinking method. From the research conducted, it is known that SIBAKUL Jogja is enough to be the answer to revive the economy for MSMEs who are still struggling through the Covid-19 pandemic to regain their market, without visiting consumers or conducting conventional transactions. However, there are obstacles that arise due to the lack of mastery of technology by some MSME actors so that they have not maximized existing programs. Thus, the Department of Cooperatives and MSMEs DIY continues to conduct various trainings or seminars to solve the problems faced.